SELF-REGULATION AND SELF-REGULATORY CAPACITIES: COMPONENTS, LEVELS, MODELS - Galina V Ozhiganova (Peoples' Friendship University of Russia (RUDN University), 2018)
In the article various definitions of self-regulation are considered. The task is to examine the notion of self-regulation and its perceptions in the Western and Russian psychology; the notion of self-regulatory capacities; the components, levels and models of self-regulation. A review of the representation of self-regulation in the Western and Russian psychology reveals that self-regulation is studied in relation to different facets of life: self-regulated learning, professional activity, health management, well-being, etc. Self-regulation is generally defined through the term "capacity" or "ability". It makes researchers comprehend the concept of self-regulatory capacities itself more deeply. The theoretical analysis of the components, levels and models of self-regulation allows us to speak about their variety, but there are the components which are general and crucial: motivation, standards (including values, morality), goal-setting, planning, ability for monitoring and self-control, capacity to evaluate and correct the results, to persist in goal attainment. It is revealed that a very important component of self-regulation - spiritual - is missing in the reviewed models, and the author proposes the two models of self-regulation where the spiritual level is included: 1) a four-level model of selfregulation; 2) a four-level model of self-regulation and self-regulatory capacities. Both models imply a higher spiritual level of self-regulation which is related to higher moral principles and based on the highest values and meanings of being. The higher self-regulatory capacities help to liberate the potential of energy for disinterested selfless service to the society. The higher self-regulatory capacities allow individuals to increase the energy resource for self-regulation and contribute to the productivity and quality of life.